Reserve Requirements and Monetary Management : An Introduction. (IMF Working Papers; Working Paper ;, 1993)
Reserve requirements are widely used by central banks as a means to improve monetary control, an instrument for policy implementation, a source of revenue, and a safeguard of bank liquidity. The effectiveness of reserve requirements in fulfilling these functions is reviewed, and the detailed modalities of their use are examined. Reserve requirements in a sample of developing countries are described.